Oxide Thin Films, Multilayers, and Nanocomposites - Mele, P (Springer, 2016)
This book provides a comprehensive overview of the science of nanostructured oxides. It details the fundamental techniques and methodologies involved in oxides thin film and bulk growth, characterization and device processing, as well as heterostructures. Both, experts in oxide nanostructures and experts in thin film heteroepitaxy, contribute the interactions described within this book.